Re-Mapping Russia from the Viewpoint of Foreign Investors - Applying a Self-Organizing Map in the Context of Russian Regions - Jumpponen, Jari; Ilonen, Jarmo; Laakkonen, Venla (Ekonomika, 2005)
When a foreign company enters Russia, it has plenty of choices for choosing a favourable location. A country with 17 million square kilometres, 33 cities with more than 0,5 million inhabitants and 89 different administrative regions contains a wide selection of alternatives. Even though these 89 regions have different resources, there are apparent similarities when comparing their socio-economic indicators, which in turn describe the business environment where a company operates.This paper analyses the regional economic similarities (and dissimilarities) of the 89 Russian regions from the viewpoint of a foreign investor. The aim is to test how Russian regions could be categorized by using the self-organizing map (SOM) method (Kohonen, 1995). The SOM is a hierarchypreserving non-linear mapping, which can organize similar regions close to each other based on their numerical data. In addition, the SOM has many beneficial properties, such as tolerance of incomplete and missing data, and it has been successfully used in similar tasks, such as in forecasting bankruptcies, future prices, workplace behaviour and energy use (Wong, 1996). The goals of this paper are to find out: 1) what Finnish companies are seeking when investing in Russia (market, resource, efficiency, strategic asset); 2) which are the most decisive external factors affecting the investment decision-making; and 3) whether utilizing self-organizing maps (SOM) are adequate in analyzing the Finnish enterprises’ investment decision-making grounds in Russian regions.In this study we utilize some 50 socio-economic indicators provided by the Russian State Statistics Committee, Goskomstat. Since not all the indicators are of equal weight in the decision-making process of a foreign investing company, in this study we conducted a survey among Finnish enterprises in order to find out the reciprocal dynamics of these indicators. On the basis of these results, the Russian regions will be categorized by utilizing the SOM. Thus, in comparison to existing investment potentiality ratings (see for example RAExpert, 2002), this study provides a unique and valuable insight into Russian regions from the viewpoint of investing Finnish enterprises. This study of Russian regions, applying self-organizing maps, provides a useful insight into the understanding of the uniqueness of Russian regional economic discrepancies.